In vitro bioequivalence study of paracetamol tablets locally marketed (Journal of Hama University, 2021)
Pharmaceutical preparations are bioequivalent when they have the same drug substance, dosage, and pharmaceutical form, and exhibit the same bioavailability when applied to patients under the same conditions. The bioequivalence of pharmaceutical preparations is an important indication for the possibility of interchanging between these preparations by the doctor or pharmacist. In this research, in vitro study of the bioequivalence of paracetamol tablets was performed for several local pharmaceutical companies in comparison with Brand tablets of the original company, after conducting quality control tests on them. Paracetamol was chosen as a drug model because it is one of the most widely used pain relievers and antipyretics, in addition to being one of the drugs that are widely prescribed by pharmacists without a prescription. All tablets were subjected to tests of external appearance, sealing, hardness, friability, uniformity of weight and disintegration time. The dissolution rate test was also performed, which is considered one of the most important in vitro tests to assess the bioequivalence. The release of paracetamol from the tablets and its dissolution in the medium of application over time was studied, and then calculate the similarity and dissimilarity factors of pharmaceutical preparations and thus judge their bioequivalence. The results of this research showed that all studied paracetamol tablets are bioequivalent, which allows the possibility of interchanging between these preparations by the doctor or pharmacist.